The Governmentality of Rural Household Waste Management Practices in Ala Ajagbusi, Nigeria - Saheed Adebayo Abdulwakeel; Orjan Bartholdson (Social Sciences, 2018)
There is a gap in the literature linking waste management practices to social theory. This paper attempts to bridge this gap through a study of waste management practices in Ala Ajagbusi village, Nigeria. The study explores how members of households in Ala Ajagbusi handle waste. The relevant themes of the empirical findings are categorized and linked to a social theory, Michel Foucault’s governmentality. The aim was to investigate how members of the households handle and make sense of their waste management practices. This research adopts a qualitative approach and is inspired by phenomenology. These are the bedrocks upon which the data collection methods are chosen and the interview questions are informed accordingly. The results show that villagers collectively, every week in a rotational manner, sweep their households, dispose of, and burn waste in public spaces. Villagers walk some miles from their households before they can empty their waste receptacles. Sometimes waste management behaviours are adjusted to seasonal variations. The findings also show that the villagers have no engagement with the state and local government concerning waste management. The results are linked to social theory to understand the waste management behaviours of villagers in Ala Ajagbusi.